Enzyme Aided Processing of Oil - Bello, Ibrahim; Rasaq, Nurudeen; Adeniyi, Adewale; Hammed, Ademola (International Journal of Halal Research, 2021)
Enzyme aided process (EAP) has been identified as a viable alternative for oil extraction. This paper reviews the recent trends in EAP of soybeans during degumming, transesterification, oil extraction, and demulsification. The “common protease effect” and the degree of demulsification of oil was also examined. EAP has improved overall oil yield to about 90% and high oil quality. EAP oils have high tocopherol content, decreased turbidity, higher color index, better oxidative stability, and drastic reduction in residual phosphorus content of oils thus contributing to enhanced oil quality. We conceptualize “Common enzyme effect” as the reason for degree of demulsification (oDem) occurring during enzyme aided extraction. The equation for rate of change of oDem have also been proposed. Few studies on simultaneous EAP have shown the efficacy of multifunctional enzyme to enhance oil recovery and quality. The use of immobilized enzyme has also received less attention, though, could potentially reduce EAP cost.